The Baltic Sea southern coast and the interior. Selected problems - Błażejewski, Artur (Archaeologia Lituana, 2015)
In the studies on the Baltic Sea region in the Roman period a prominent role play works concerning contacts between the south Baltic coast and areas situated more to the south. Previous publications generally dealt with two main aspects of these contacts. The first one was focused on the problem of relations of the Baltic coast with the south along the amber route. Of course, the researcher of outstanding merit was here Jerzy Wielowiejski, the author of many valuable publications whose findings are mostly still valid (1970; 1980). Their value lies primarily in discussing the nature of trade between ‘peoples of the north’ on the one hand, and Roman provinces, particularly the Danube ones, and Italia on the other hand. To the works of J. Wielowiejski publications of other authors also referred. [...]